1993
DOI: 10.3109/00498259309059441
|View full text |Cite
|
Sign up to set email alerts
|

The disposition and metabolic fate of14C-meropenem in man

Abstract: 1. The metabolism and pharmacokinetics of 14C-meropenem were studied in five volunteers who received 0.5 g (40 microCi) of the radiolabelled drug by i.v. infusion. 2. The maximum concentration of drug in plasma was 27 +/- 2 micrograms/ml (70 microM) corresponding to 98% of plasma radioactivity at the end of a 30 min infusion. The elimination half-life for meropenem in plasma was 1 h and meropenem remained the major radioactive component up to 6 h, but represented a decreasing proportion of the plasma radioacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
1

Year Published

1997
1997
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 11 publications
1
17
1
Order By: Relevance
“…These carbapenems share generally dose-proportional pharmacokinetics over marketed dose ranges and a short elimination half-life of approximately 1 h. Ertapenem differs, with a high level of protein binding and consequently a nonlinear pharmacokinetic profile and a longer half-life than that of doripenem (Ivanz [ertapenem for injection] U.S. prescribing information; Merck & Co. Inc., February 2008). The disposition of doripenem, reported in this study, is comparable to that of other carbapenems, including imipenem/ cilastatin, meropenem, and ertapenem (4,8,16,18; U.S. prescribing information for Ivanz). The total radioactivity of doripenem in plasma paralleled the plasma carbapenem concentration shortly after infusion of a 14 C-labeled carbapenem.…”
Section: Discussionmentioning
confidence: 48%
“…These carbapenems share generally dose-proportional pharmacokinetics over marketed dose ranges and a short elimination half-life of approximately 1 h. Ertapenem differs, with a high level of protein binding and consequently a nonlinear pharmacokinetic profile and a longer half-life than that of doripenem (Ivanz [ertapenem for injection] U.S. prescribing information; Merck & Co. Inc., February 2008). The disposition of doripenem, reported in this study, is comparable to that of other carbapenems, including imipenem/ cilastatin, meropenem, and ertapenem (4,8,16,18; U.S. prescribing information for Ivanz). The total radioactivity of doripenem in plasma paralleled the plasma carbapenem concentration shortly after infusion of a 14 C-labeled carbapenem.…”
Section: Discussionmentioning
confidence: 48%
“…[13] Most of the antibiotics used for treatment in this study are mainly eliminated via the urinary tract, and the amount of antibiotics found in faeces is often low (approximately 1-5%) [14][15][16][17][18][19]. An exception to this in our study is ertapenem where about 10% of the dose is found in the faeces [20].…”
Section: Discussioncontrasting
confidence: 46%
“…Further increasing the pH of the buffer solution caused the reduction peak current to decrease. Furthermore, within the pH range of 2.0 to 6.0, the reduction peak potential increased gradually, whereas from 6.0 to 8.0 it decreased gradually, indicating a low electron transfer rate [22].…”
Section: Effect Of Phmentioning
confidence: 99%
“…
Harrison et al [22] studied the metabolism of meropenem and *Corresponding author: Sreedhar NY, Electroanalytical Lab, Department of Chemistry, Sri Venkateswara University, Tirupati-517502, Andhra Pradesh, India, Tel: +91-9440087124; E-mail: sreedharny.chem@gmail.com
AbstractThe theme of this study was the preparation, characterization, and application of a polyaniline (PAN) and graphene composite modified glassy carbon electrode (PAN/Gr/GCE) for the voltammetric determination of doripenem (DPM) and meropenem metabolites (MPM) in human urine and serum samples. The morphological study of the PAN/ Gr/GCE composite was examined by scanning electron microscopy (SEM) and cyclic voltammetry (CV).
…”
mentioning
confidence: 99%
See 1 more Smart Citation